Pelatihan Pembuatan Izin Pangan Industri Rumah Tangga (P-Irt) di Desa Ulapato - Asral Kelvin Sahrain (LP2M IAIN Sultan Amai Gorontalo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the food sector in Ulapato Village, Telaga Biru possess substantial potential for development, yet are constrained by limited understanding of the importance of Home Industry Food Permits (P-IRT). The P-IRT permit serves as a crucial requirement for enhancing business legality, consumer confidence, and competitiveness of local food products. This community service program aims to provide comprehensive training to MSME actors regarding the procedures for P-IRT permit application, encompassing administrative requirements and food safety standards. The implementation methods include lectures, interactive discussions, and practical assistance in document preparation. The program was conducted on July 20, 2025, with 30 participants from food MSMEs in Ulapato Village. The results demonstrate a significant improvement in participants' understanding of P-IRT procedures, with 90% of participants indicating comprehension of the requirements and application stages. Furthermore, 25 participants (83%) committed to processing their P-IRT permits within the subsequent three months. This program yields positive impacts in promoting the formalization of home-based food enterprises and enhancing MSME actors' awareness regarding the significance of food safety and product legality.